(untitled) (Bulletin KNOB, 2023)
In several academic disciplines that focus on (historical) building practice there is growing interest in building contractors and their employees. Their contribution and influence are increasingly the subject of research. After the Second World War the contractor’s field of work was defined by productivity, specialization and industrialization, which profoundly altered the professional character of this branch of industry. Social developments and the prevailing idea of an all-encompassing welfare state triggered top-down and bottom-up changes in this traditionally highly cyclical sector. This fostered diversity in the contracting world, yet those diverse profiles and identities often remain unrecognized today. This is compounded by the fact that, unlike architects for example, the source material left behind by contractors and their employees is usually less informative and often fragmented. This article seeks to demonstrate the potential of alternative source material by analysing company photos in order to better understand the profile and identity of two post-war Belgian contractors. During their existence, Van Coillie of Oostende (1919-1976) and Van Laere of Kruibeke (1938-1989) amassed extensive collections of photographs, which were recently made accessible by the Flanders Architecture Institute (VAi). The focus of this article is on a series of photos from the 1960s and ’70s depicting the headquarters of both companies. These company premises and buildings were the very heart of the businesses, which adopted a pragmatic or strategic design to reflect their profile and identity. The selected photos are compared with information gleaned from a series of in-depth interviews with ex-employees in order to place the companies in their particular historical context. The analysis is in two parts, the first of which focuses on the site, the company architecture and the implanting. This reveals information about the size and organization of the contractors, as well as about their company strategy and professional profile. For example, they used these elements to create a strong position in the building sector and in so doing cement their reputation. The second part analyses a few interiors of the 1961 Van Laere headquarters. A detailed visual examination reveals how these spaces reflected the internal organization and hierarchical structure and how Van Laere projected its company image both internally and externally. The pictures also chart the development of an organizational culture and a body of values and norms that in turn shaped the company identity. The company management, the internal organization and the social and local network in which the firms were embedded, consequently had a considerable effect on the position they occupied as individual players in building practice. The main finding from these two analyses is that these post-war construction players were highly diverse. A critical and biographical sketch in terms of activities, profile and identity is consequently a necessary starting point for a detailed analysis of their position and role within national and international post-war building practice. This article shows what a rich source photographic material can be in developing such a sketch.